KAJIAN YURIDIS PEMBERIAN IZIN PERKAWINAN ANAK DI BAWAH USIA MINIMUM - Daulay, R. Fahmi Natigor; Evangelista, Beverly (Universitas Kapuas, 2025)
Marriage constitutes a sacred bond between men and women governed by the Indonesian legal system. Law No. 16 of 2019 establishes a minimum marriage age of 19 years for both men and women, yet provides exceptions through marriage dispensation mechanisms for those who have not reached that age. This research examines the juridical aspects of granting marriage permits for children below the minimum age through normative juridical methods with qualitative analysis of statutory regulations and legal literature. Research findings indicate that marriage dispensation is regulated under Article 7 paragraph (2) of the Marriage Law and Supreme Court Regulation No. 5 of 2019, with contributing factors including economic aspects, low education levels, and cultural traditions. Underage marriage generates negative impacts including school dropout, reproductive health disorders, and sustained poverty. Strengthened regulations and comprehensive prevention efforts are required to protect the best interests of children.